Effects of graphene content on formation and characteristics of char layer in intumescent coating - Hong, Phan Ngoc; Hong, Nguyen Tuan; Duc, Nguyen Anh; Tu, Nguyen Thi Ngoc; Duan, Le Van; Ninh, Vu The; Trang, Tran Thu; Lien, Nguyen Thi; Ly, Giang Thi Phuong; Nguyen Viet, Dung (Vietnam Journal of Science and Technology, 2024)
This study provides a better understanding of the role and mechanism of graphene nano-platelets used as a flame-retardant filler in a commercial intumescent acrylic-based formulation. Through thermogravimetric analysis, the morphology and mechanical properties of the char layer as well as the influence of graphene on the expansion ratio and compression force are clarified. The achieved results demonstrate that graphene accelerates the burning of the coating and affects the structure of the char layer. The fire test was carried out in an electric furnace at a temperature of up to 800 °C for our fabricated samples, the swelling images show that the expansion ratio of the graphene-loaded coating is lower than that of the coating without graphene. On the other hand, during the combustion, the speed of air release occurring in a short time also contributes to forming bigger holes in the char layer, so the hardness of the graphene-loaded char layer is lower than that of the char layer without graphene coating.